2017
DOI: 10.1007/s11192-017-2359-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the coevolution between citations and coauthorship of scientific papers

Abstract: Collaborations and citations within scientific research grow simultaneously and interact dynamically.Modelling the coevolution between them helps to study many phenomena that can be approached only through combining citation and coauthorship data. A geometric graph for the coevolution is proposed, the mechanism of which synthetically expresses the interactive impacts of authors and papers in a geo-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The model provides an example of how individual strategies based on positive benefit-minus-cost and on specific randomness generate the complexity emerged in coauthorship networks. It can be extended to analyze the coevolution with citation behavior [25]. It also has the potential to be a null model in the empirical analysis of social affiliation networks.…”
Section: Discussionmentioning
confidence: 99%
“…The model provides an example of how individual strategies based on positive benefit-minus-cost and on specific randomness generate the complexity emerged in coauthorship networks. It can be extended to analyze the coevolution with citation behavior [25]. It also has the potential to be a null model in the empirical analysis of social affiliation networks.…”
Section: Discussionmentioning
confidence: 99%
“…Does it mean sociable researchers (with many collaborators) will preferentially coauthor with other sociable researchers, and unsociable to unsociable? In a previous study [48], we showed that the proportion of top 5.99% most sociable authors (measured according to degree) having coauthored with another such author is 99.5%. The proportion may even be underestimated, because these authors probably coauthored before 1999 or in other situations.…”
Section: Availability Of Data and Materialsmentioning
confidence: 82%
“…3 in Ref. [34]). In fact, signing on a paper of a famous journal will also bring about a huge benefit.…”
Section: Cooperation Cost and Reputation Benefitmentioning
confidence: 91%
“…Coauthorship relationship can be expressed by a hypergraph, where nodes represent authors, and the author group of a paper (called it a "paper team") forms a hyperedge. A number of models have been proposed for generating hypergraphs in specific random ways, and some of them have been used for modelling coauthorship networks [32][33][34]. Meanwhile, there has been an amount of previous work on the structures of specific random hypergraphs, such as clustering, the emergence of a giant component, and so on [35][36][37][38].…”
Section: The Modelmentioning
confidence: 99%